Advanced exergy and exergoeconomic analyses and a case study of a novel trans-critical CO2 cycle with pressurization process for hot dry rock. (15th October 2021) - Meng, Nan; Li, Tailu; Kong, Xiangfei; Gao, Xiang
Highlights: The influence of initial parameters on power generation system is studied. The system is evaluated by the advanced exergy/ exergoeconomic method. The results of conventional and advanced exergy analysis method are compared. Condensers and intercoolers have great potential for performance improvement. The investment cost is the main factor affecting the economic performance. Abstract: Using hot dry rocks instead of fossil fuels can greatly alleviate the problem of environmental pollution. However, the low thermoelectric conversion efficiency of dry hot rock resources may hinder its commercial development. Therefore, an in-depth analysis of the operating efficiency and the relationship between the components in the hot dry rock power generation system can provide a basis for improving the system performance. In this study, the influence of the initial operating parameters on the thermodynamic performance of a trans-critical CO2 cycle with pressurization process applied to the utilization of hot dry rock resources is analyzed, so as to make the system more universal. On the other hand, the thermo-economic performance of the system is evaluated by traditional and advanced exergy/ exergoeconomic analysis respectively. The results show that the increase in production well-head temperature and CO2 capture pressure, the decrease in the CO2 capture temperature will improve the thermodynamic performance of the system to a certain extent. In general, the ratio of endogenous avoidable exergy destruction in trans-critical CO2 generation cycle and CO2 pressurization process is 46.48% and 34.41%, respectively. The exergy efficiency of condensers and intercoolers in the system is low, which have high performance improvement potential. The exergoeconomic analysis shows that the investment cost of each component is the main factor affecting the economic performance. Meanwhile, advanced exergy/ exergoeconomic analysis provides the valuable information for a clearer understanding of the interactions between different components of the system and the potential for improvement.